2014
DOI: 10.1002/chem.201403960
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Scandium Ions to Metalloporphyrin–Flavin Complexes for Long‐Lived Charge Separation

Abstract: A porphyrin-flavin-linked dyad and its zinc and palladium complexes (MPor-Fl: 2-M, M=2 H, Zn, and Pd) were newly synthesized and the X-ray crystal structure of 2-Pd was determined. The photodynamics of 2-M were examined by femto- and nanosecond laser flash photolysis measurements. Photoinduced electron transfer (ET) in 2-H2 occurred from the singlet excited state of the porphyrin moiety (H2 Por) to the flavin (Fl) moiety to produce the singlet charge-separated (CS) state (1) (H2 Por(.+) -Fl(.-) ), which decaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…H 2 DPP, [47,83] Me 5 Fc [84] and TBABPh 4 [85] were synthesized according to the reported procedure. TFAa nd Fc derivatives (Fc, Me 2 Fc, Me 8 FC, and Me 10 Fc) were purchased from commercial sources and were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 DPP, [47,83] Me 5 Fc [84] and TBABPh 4 [85] were synthesized according to the reported procedure. TFAa nd Fc derivatives (Fc, Me 2 Fc, Me 8 FC, and Me 10 Fc) were purchased from commercial sources and were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…TFAa nd Fc derivatives (Fc, Me 2 Fc, Me 8 FC, and Me 10 Fc) were purchased from commercial sources and were used without further purification. H 2 DPP, [47,83] Me 5 Fc [84] and TBABPh 4 [85] were synthesized according to the reported procedure. All measurements were performed at 120 Ko naBruker APEXII Ultra diffractometer.T he structures were solved by ad irect method (SIR-97) and expanded with differential Fourier techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Pd porphyrin (PdP)‐flavin‐linked dyad also has the large positive shift in the one‐electron reduction potential of the Fl moiety from −0.77 V vs. SCE to +0.21 by binding two Sc 3+ ions to the Fl moiety . The photoinduced electron transfer in the PdP‐Fl‐(Sc 3+ ) 2 complex afforded the triplet‐charge‐separated state ( 3 [PdP .+ ‐Fl .− ‐(Sc 3+ ) 2 ]), which has the remarkably long lifetime of 110 ms …”
Section: Flavin Photoredox Catalystsmentioning
confidence: 99%
“…In a number of electron transfer systems, it has been shown that the driving force of electron transfer is tuned by complexation of radical anions, produced in electron transfer reactions, with metal ions that act as Lewis acids. 11,12 In the area of light energy harvesting, the generation of longlived electron transfer products during the process of photoinduced electron transfer (PET) is indispensable for converting light energy into other forms as observed in photosynthesis, 13,14 solar cells, 15,16 and photocatalysis for fuel production. 17−19 In plant photosynthesis, photoexcitation of "special pair" chlorophylls in a well-organized donor−acceptor (DA) sequence in photosystem II triggers a series of electron transfer (ET) reactions in which the rates and direction of ET are governed by metal ions bound to quinones.…”
Section: ■ Introductionmentioning
confidence: 99%